Emerging strategies for nitric oxide production and their topical application as nanodressings to promote diabetic wound healing - Dan Xia; Ying Guo; Ruodan Xu; Ning Li (Journal of Nanobiotechnology)
Abstract The challenges associated with prolonged healing or non-healing of chronic diabetic wounds contribute significantly to the increased incidence of lower limb amputation. A pivotal factor in the impediment of healing is the reduced production of endogenous nitric oxide (NO) due to the hyperglycemic microenvironment typical of chronic diabetes. While both endogenous and exogenous NO have been shown to promote the healing process of diabetic wounds, the direct application of NO in wound management is limited due to its gaseous nature and the risk of explosive release. This review summarizes recent advances of nanodressings incorporating NO donors in the treatment of diabetic wounds, detailing the specific conditions under which these nanodressings facilitate NO release, with a focus on the beneficial effects of NO, strategies for its supplementation, and the challenges encountered in the clinical translation of NO donors as a clinically viable nanomedicine in the context of improving diabetic wound healing. Graphical Abstract